SMOKE CONTROL OF A CAR PARK BY MEANS OF CFD ANALYSES USING JET FANS - Celen, Ali; Kundu, Balaram; Dalkilic, Ahmet Selim; Kayaci, Nurullah; Atayilmaz, Sevket Ozgur; Wongwises, Somchai (AMER SOC MECHANICAL ENGINEERS, 2014)
Analysis and interpretation of daily emission ventilation with fire ventilation systems in indoor parking lots coupling with jet fans have been done by a CFD program. The ventilation of an eight-story parking lot in Istanbul is carried out and the investigation for a simplified one-story of this system is also considered. The placement of jet fans has been identified on the basis of eliminating dead jones in the passage with the help of air flow analysis. Therefore, the present study may be of great importance as both the fire and smoke can be evacuated effectively by using the optimal position of jet fans in the parking lots to maintain a less polluted atmosphere inside.
Keywords: Engineering